22. EFFICACY OF VAGINAL ERBIUM LASER IN THE TREATMENT OF GENITOURINARY SYNDROME OF MENOPAUSE (Vietnam Journal of Community Medicine, 2024)
Introdution: Genitourinary syndrome in menopause pose a great threat to quality of life due to change of genital, sexual, urological symptoms because of estrogen deficiency. The evidence for stricture rates following robot-assisted radical cystectomy (RARC) is limited. We evaluated the efficacy of vaginal erbium laser in the treatment of genitourinary syndrome of menopause at Binh Dan hospital. Methods: All patients were treated with 2,940 nm Er:YAG laser (FotonaSmooth®) from January 2023 through March 2024 at Binh Dan hospital. Symptoms will be evaluated before and after therapy for 6 months using the VAS, VHIS and ICIQ-UI SF scales. Results: Follow-up period was 6 months. We conducted a study with 72 participants. The average age of the sample size was 60.4 with age at menopause around 48, around 56% of the participants suffered from Stress Urinary Incontinence. Vaginal erbium laser treatment induced a significant (p < 0.01) decrease in VAS for both vaginal dryness and dyspareunia, as well an increase in VHIS (p < 0.01) and improved mild-moderate stress urinary incontinence in 40 postmenopausal women up to the 6th month after the last laser treatment. About 1% of patients had adverse events. Conclusion: These results suggest that vaginal erbium laser may be effective and safe for the treatment of genitourinary syndrome of menopause.
Keywords: Genitourinary syndrome of menopause, vaginal erbium laser.